(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the essence and components of creative management in the system of strategic management of changes and development of the enterprise’s competitiveness. The works of Ukrainian and foreign scientists devoted to the issues of creativity, competitiveness and strategic management of changes and development, considered by them from the point of view of philosophical, psychological, pedagogical, sociological, economic and strategic analysis, were studied and analyzed. A clear interaction of concepts such as "competitiveness", "creative management", "strategic management of changes and development" was determined. The most common criteria for strategic management of changes and development of the enterprise’s competitiveness within the framework of creative management are highlighted. Accordingly, similarly to the criteria of creative management, the main criteria of strategic management of changes and development of the enterprise’s competitiveness within the framework of creative management were defined. The division of competitiveness factors into external and internal was carried out, in relation to the strategic management of changes and development of the enterprise’s competitiveness. The main indicators of the enterprise’s activity and the components of creative management are proposed, which will form its system of strategic management of changes and development of competitiveness, which should include the following creative components, such as: intelligence and knowledge; experience and communications; creative abilities of employees; willingness to experiment; motives and incentives; critical thinking and self-assessment. They are related to the performance indicators of the enterprise, namely: financial indicators; staff productivity; new business models; corporate culture; innovation management; competitive advantages and strategies. The scheme of creative management in the system of strategic management of changes and development of competitiveness of the enterprise was formed, which will include the main indicators of the effectiveness of its activity, the constituent elements of creative management and strategic management of changes and development of competitiveness.